The Effect Of Technology Characteristics In The Continued Use Of Charity Crowdfunding Platforms Through Trust And User Satisfaction - Almuntaha, Eska; Rahmawati, Nur (UNIB Press, 2023)
This research's objective is to examine the effect of technological characteristics on trust and satisfaction in using a charity crowdfunding platform so that the user will reuse the platform. The use of technology in excellent and sustainable online donation fundraising requires the fulfilment of technological characteristics. A study by Bhattacherjee (2001)) stated that continued use influences information technology's success. Another significant area in information systems research is user satisfaction because it is an essential factor in measuring the use and success of an information system (Bailey and Pearson, 1983; Ives et al., 1983; Doll and Torkzadeh, 1988; Delone and McLean, 1992 in Roca et al., 2006). This study used the purposive sampling method and tested the hypothesis using the Structural Equation Model (SEM). This research proves that trust affects the satisfaction of using a charity crowdfunding platform, but not with technological characteristics. Meanwhile, users' satisfaction influences continued use but not trust. Keywords: Technology Characteristics, Continued Use, User Satisfaction, User Trust, Charity Crowdfunding Platform.